Glucose patterns following alcohol and illicit drug use in young adults with type 1 diabetes: A flash glucose monitoring study. Issue 3 (6th May 2021) - Pastor, Adam; Conn, Jennifer; Loh, Margaret; O'Brien, Casey L; Teng, Jessie; Finch, Sue; Collins, Lisa; MacIsaac, Richard J; Bonomo, Yvonne
Abstract: Introduction: To assess the effects of alcohol and illicit drug use in young adults (age 18–35) with type 1 diabetes (T1D) on flash glucose monitor sensor glucose (SG) readings. Methods: Twenty young adults with T1D were enrolled from a tertiary referral hospital outpatient department in Melbourne, Australia for a 6‐week prospective observational study using flash glucose monitoring (FGM). Glucometrics comparing substance using days (SUEDs) to those without substance use (non‐SUEDS) were analysed. The primary outcomes were the difference in mean SG values, its standard deviation and minutes/24‐h period out of range (SG <3.9 mmol/L or >10.0 mmol/L) between matched SUEDs vs non‐SUEDs. An interaction model with the primary effect of HbA1c on SG values was also performed. Results: There were no differences in the primary outcome measures between SUEDS and non‐SUEDs. However, there were differences in the regression coefficients for HbA1c and glucometrics between non‐SUEDs and SUEDs for mean SG, time out of range and time with SG > 10 mmol/L. This difference was also identified between non‐SUEDS and days of ≥40 g alcohol for mean SG. Conclusions: While there was no difference between glucometrics for SUEDs and non‐SUEDs on primary outcomes, HbA1C was found to be a less reliable predictor of glucose patterns in the 24‐h period following substance use than control days. Young adults with T1D need to monitor and respond to their glucose levels following substance use and engage in harm minimisation practices irrespective of baseline glucose control. Abstract : Using FGM, we found no difference in glucometrics in young adults with type 1 diabetes following days of substance use than those without. However, HbA1C values were less predictive of glucometrics on days of substance use than those without substance use. Young adults with T1D, even those with adequate glucose control, need to engage in harm reduction measures, including closer monitoring of their glucose levels, should they choose to consume alcohol or illicit drugs.